Fintech Services and Entrepreneurship in Africa - Olanrele, Iyabo (Finance & Economics Review, 2025)
Purpose: This paper examines the effect of fintech on entrepreneurship to ascertain the role of financial technology services on individual entrepreneurial intention in five sub-Saharan African countries. Methods: The analysis was based on an extended probit model to determine the country-specific effect of mobile money account ownership (Fin) on individuals who used fintech services to start a business (Ent) as a measure of entrepreneurship. The impact of other control variables (X) such as credit access, education, and labor force participation on entrepreneurship (Ent) was also considered. Results: The findings show that fintech services through mobile money are significantly associated with an increased likelihood of entrepreneurship in The Republic of Congo, Kenya, Mauritius, Nigeria, and South Africa. Credit access, higher levels of education, and labor force participation are other drivers of entrepreneurship in Kenya, Nigeria, and South Africa. Implications: Country-specific characteristics play a significant role in engendering entrepreneurship; thus, the government should intensify efforts to diffuse and adopt fintech for optimal livelihood and economic transformation. Originality: Overall, this paper accounts for the role of technology penetration in financial services and contributes to the literature on entrepreneurship development in the African context. The research utilizes the World Bank Global Findex data, which is nationally representative, to provide insight into the subject matter. Limitations: This paper's analysis relied on the 2017 World Bank Global Findex Database, the most recent data available. Although this may be perceived as insufficient, the findings were valid due to their alignment with similar outcomes in the literature